Monokulturalisme dalam Tayangan Web Series Animasi Anak Nussa - Muhammad Alzaki Tristi; Rani Attiqah Gusbet (Universitas Gadjah Mada, 2024)
The objective of this study is to demonstrate how the concepts of monoculturalism are evident in the Nussa children's web series animations. Utilizing a qualitative approach, the research involved content analysis of five specific episodes from the Nussa Official YouTube channel. The analysis employed a semiotic approach to uncover both explicit and implicit meanings. The study's framework for monoculturalism is based on the concepts outlined in